THE COMBINATION OF COMMUNICATIVE, LINGUISTIC, AND CULTURAL POSSIBILITIES IN MODERN UZBEK CHILDREN'S JOURNALS: AN EXAMPLE OF GULXAN AND G’UNCHA (Western European Journal of Linguistics and Education, 2024)
This article explores the communicative, linguistic, and cultural dimensions of two prominent Uzbek children's magazines, Gulxan and G’uncha, analyzing how they contribute to the development of young readers in contemporary Uzbekistan. The study investigates the magazines' role in integrating entertainment, education, and cultural preservation, while fostering both national identity and global awareness. Through a detailed content analysis of selected issues, the research highlights how these magazines use a mix of interactive, engaging elements, accessible language, and culturally rich content to educate children. The findings reveal how Gulxan and G’uncha balance modern influences with traditional values, ensuring young readers engage with their cultural heritage while navigating an increasingly globalized world. This study underscores the magazines' importance as tools for both cultural transmission and linguistic development in the context of modern Uzbek children's literature.